ANALISIS KEMAMPUAN MEMBACA PERMULAAN DENGAN MEDIA GAMBAR PAPAN MEMBACA SISWA KELAS II SD N PANGGANG - Munawaroh, Raden Roro Zakiyah; Purnomo, Heru (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2025)
This study aims to examine the role of visual media in supporting second-grade students at SD N Panggang in developing early reading skills. Data were collected through direct observation, in-depth structured interviews, and the analysis of relevant supporting documents. The data were analyzed using the Miles and Huberman model to gain a more comprehensive understanding of the research findings. The results indicate that the use of visual media has a positive impact on enhancing students’ early reading abilities. Significant improvements were observed in several aspects, including reading accuracy, word pronunciation clarity, and reading fluency. In addition to strengthening early reading skills, the use of the PANCA Reading Board as a visual medium also positively influenced students’ learning motivation and interest, making them more enthusiastic and actively engaged in the learning process. The study concludes that the PANCA Reading Board is an effective instructional tool for improving early reading skills among second-grade students at SD N Panggang. The findings are expected to contribute to the development of more innovative and effective early reading instructional methods. Therefore, this research can serve as a reference for educators and future researchers in designing better strategies for teaching early reading.